Senam Lansia dan Tingkat Stres pada Lansia di Dusun Polaman Argorejo Kecamatan Sedayu 2 Kabupaten Bantul Yogyakarta - Raden Jaka S; Tri Prabowo; Wahyu Dewi S (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2015)
Physical activity of elderly can be a mechanism of dealing with stress. However, older people are rarely engage in the physical activity. The purpose of this study was to know the relationship between elderly gymnastics and level stress in village of Polaman Argorejo, District of Bantul Yogyakarta. This study was an analytic quantitative research with cross sectional design. The population in this study was elderly that lived in Polaman village which totaled 90 respondents. Technique sampling used was total sampling resulted on 90 respondents. The analysis used was chi-square. Results showed that elderly who actively participated in gymnastic and not stress was 16 respondents (76,2%), while elderly who actively participated in gymnastic and stress was 5 respondents (23,8%), there was a signiﬁ cant relationship between gymnastic and the level of elderly stress with value of p=0,000. In conclusion, there was a signiﬁ cant relationship between gymnastics for the elderly and stress level on elderly in Polaman village Argorejo Bantul Yogyakarta.